Strategi Sekolah dalam Menumbuhkan Kemampuan Kepemimpinan Siswa di SMP Negeri 3 Surabaya - Suwardani, Anissa Rizki; Mustika Kartika Sari, Maya (Kajian Moral dan Kewarganegaraan, 2025)
Developing leadership skills in students is an important thing that must be developed in every child as early as possible because students are future leaders. The purpose of this study is to describe the school's strategy in developing student leadership skills at SMP Negeri 3 Surabaya and to describe the supporting and inhibiting factors in developing leadership skills. This study uses the Situational Leadership Theory by Kenneth W. Blanchard and Paul Hersey. This study uses a qualitative research design with a case study approach. The determination of the research subjects used a purposive sampling technique and the subjects of this study were the OSIS supervisor, the Vice Principal of Student Affairs, and the OSIS administrators. Data collection techniques through observation, interviews, and documentation. Data analysis used data collection techniques, data reduction, data presentation, and drawing conclusions. The results of the study showed that the strategy used by the school in developing student leadership skills at SMP Negeri 3 Surabaya was by implementing the School Environment Introduction Period (MPLS) which was followed by all students as a mandatory program, recruitment of strict student organization management through a two-stage selection system, inauguration of Student Leadership Basic Training (LDKS) involving external practitioners of the school, and involvement of OSIS administrators in taking responsibility for school activities. Supporting factors in the growth of student leadership at SMP Negeri 3 Surabaya are the commitment of the principal, experienced teachers, cooperation with external parties of the school, and parental support. Inhibiting factors in the growth of student leadership at SMP Negeri 3 Surabaya are students' difficulties in dividing time between school learning and activities outside of learning and lack of interest and motivation in students.